Circulating microRNA sequencing revealed miRNome patterns in hematology and oncology patients aiding the prognosis of invasive aspergillosis - Gábor Fidler; Anna Anita Szilágyi-Rácz; Péter Dávid; Emese Tolnai; László Rejtő; Róbert Szász; Szilárd Póliska; Sándor Biró; Melinda Paholcsek (Scientific Reports, 2022)
Abstract Invasive aspergillosis (IA) may occur as a serious complication of hematological malignancy. Delays in antifungal therapy can lead to an invasive disease resulting in high mortality. Currently, there are no well-established blood circulating microRNA biomarkers or laboratory tests which can be used to diagnose IA. Therefore, we aimed to define dysregulated miRNAs in hematology and oncology (HO) patients to identify biomarkers predisposing disease. We performed an in-depth analysis of high-throughput small transcriptome sequencing data obtained from the whole blood samples of our study cohort of 50 participants including 26 high-risk HO patients and 24 controls. By integrating in silico bioinformatic analyses of small noncoding RNA data, 57 miRNAs exhibiting significant expression differences (P < 0.05) were identified between IA-infected patients and non-IA HO patients. Among these, we found 36 differentially expressed miRNAs (DEMs) irrespective of HO malignancy. Of the top ranked DEMs, we found 14 significantly deregulated miRNAs, whose expression levels were successfully quantified by qRT-PCR. MiRNA target prediction revealed the involvement of IA related miRNAs in the biological pathways of tumorigenesis, the cell cycle, the immune response, cell differentiation and apoptosis.